2017
DOI: 10.1002/kin.21143
|View full text |Cite
|
Sign up to set email alerts
|

Shock‐Tube Experiments and Kinetic Modeling of CH3NHCH3 Ignition at Elevated Pressures

Abstract: Ignition delay times of CH3NHCH3/O2/Ar mixtures are measured with a shock tube in the temperature range of 1040–1604 K. Different pressures (4, 8, and 18 atm) and equivalence ratios (0.5, 1, and 2) are investigated. A recently developed CH3NHCH3 kinetic model is examined, and then modified by adding the hydrogen abstractions from CH3NHCH3 by HO2 and NO2. The rate constants of the hydrogen abstraction by HO2 are estimated by analogy to the CH3OH + HO2 system, and those of the hydrogen abstraction by NO2 by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Ignition delay time is a key combustion parameter, helpful to evaluate the kinetic model and understand the combustion chemistry of fuels. Li et al 5 and Shi et al 8 both measured the ignition delay times of DMA using shock tubes within the combustion temperature range of 1140–1604 K. Li et al proposed a kinetic model which has a good performance in predicting the ignition delay times of DMA under fuel-lean conditions but overestimates the values under fuel-rich conditions. The possible reason is that the reactions between DMA and NO 2 are neglected in the model of Li et al In order to validate the importance of these reactions, the model of Li et al is updated with our calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ignition delay time is a key combustion parameter, helpful to evaluate the kinetic model and understand the combustion chemistry of fuels. Li et al 5 and Shi et al 8 both measured the ignition delay times of DMA using shock tubes within the combustion temperature range of 1140–1604 K. Li et al proposed a kinetic model which has a good performance in predicting the ignition delay times of DMA under fuel-lean conditions but overestimates the values under fuel-rich conditions. The possible reason is that the reactions between DMA and NO 2 are neglected in the model of Li et al In order to validate the importance of these reactions, the model of Li et al is updated with our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…In their work, DMA was regarded as the prototype of nitrogen-containing biomass to explore the fuel-nitrogen conversion, and NO 2 was produced noticeably at the initial stage. Li et al 5 and Shi et al 8 both investigated the combustion chemistry of DMA by measuring its ignition delay times in shock tubes and Shi et al 8 found that the H-abstraction reactions from DMA by NO 2 are important during the DMA autoignition. Recently, Pappijn et al 9 reviewed the combustion chemistries of several amines including DMA, and found that these amines are key precursors for HCN and NO x .…”
Section: Introductionmentioning
confidence: 99%
“…Fuel-related reactions, reaction R966, CH 3 NHCH 3 + H = CH 3 NHCH 2 + H 2 , and reaction R970, CH 3 NHCH 3 + OH = CH 3 NHCH 2 + H 2 O, inhibit ignition through consuming reactive H and OH radicals, and the inhibition may also arise from the common product, CH 3 NHCH 2 . Our previous study demonstrated that CH 3 NCH 3 can react with O 2 , yielding CH 3 and NO, while one consuming pathway for CH 3 NHCH 2 produces HCN by consuming reactive radicals (such as OH, O, and CH 3 ) and H atoms. NO can promote ignition through reaction R1104. ,,,,,, Reactions R129, R175, and R128, which are also among the most inhibiting reactions for neat CH 4 , inhibit the ignition process of CH 4 /CH 3 NHCH 3 mixtures by consuming OH radicals, CH 3 radicals, and H atoms, respectively.…”
Section: Kinetic Models and Analysesmentioning
confidence: 99%
“…In the following discussion, the numbers in the parentheses indicate the molar fractions of corresponding species. The reaction pathways for neat CH 4 and neat CH 3 NHCH 3 were detailed previously. ,, Therefore, we will focus on the effect of CH 3 NHCH 3 addition on the reaction pathway of CH 4 .…”
Section: Kinetic Models and Analysesmentioning
confidence: 99%
See 1 more Smart Citation